Hidrokimia Mata Air Karst untuk Irigasi Studi Kasus Desa Ligarmukti, Kabupaten Bogor - Rizka Maria; Ananta Purwoarminta; Rachmat Fajar Lubis (Jurnal Irigasi, 2018)
Ligarmukti Village in Bogor Regency is a karst hilly area that is rich in springs so that it can supply water for domestic and agricultural purposes. The chemical properties of water derived from limestone have their own characteristics which probably have an impact on the quality of agricultural products. Thus, this study was conducted to analyze the hydrochemical properties of karst springs for irrigation. Research methods were secondary data inventory, hydrogeological observation, and laboratory analysis. Sodong is the largest spring with a discharge of 314.42 l/s in the rainy season and 154.38 l/s in the dry season. Rice field area is approximately 300 ha. The discharge from the spring can irrigate rice fields covering an area of 314.14 ha in the rainy season and 154.38 ha in the dry season. In addition to discharge, water chemical factors also determine agricultural yields. Groundwater hydrochemical including Ca-HCO3 facies, groundwater flow systems are controlled by autogenic recharge which shows the type of water in the spring from rainwater directly infiltrated in the area. Classification of water for irrigation including C2-S1 type which shows that spring has good water quality, a risk of medium salinity, and low sodium risk. The results of this study can be used by the government to maintain the village of Ligarmukti as an agricultural granary.